Examining local food procurement, adaptive capacity and resilience to environmental change in Fort Providence, Northwest Territories - Ross, Paulina Paige (Author); Mason, Courtney (cmason) (Thesis advisor); Tsigaris, Peter (ptsigaris) (Degree committee member); McCormick, Rob (rmccormick) (Degree committee member); Wesche, Sonia (Degree committee member); Thompson Rivers University Faculty of Science (Degree granting institution) (Thompson Rivers University, 2019)
Rural Indigenous communities across northern Canada are experiencing high rates of food insecurity as a result of interconnected socio-cultural, economic and environmental challenges. The loss of traditional ecological knowledge, high costs of market foods and lack of infrastructural capacity are creating multifaceted barriers for isolated, northern communities. Climate change is impacting the ability of northern Indigenous communities to acquire, access and utilize food that is culturally relevant and sustainable. This research explores local food procurement activities in the community of Fort Providence, Northwest Territories. The objective of this research was to consult with key community members to understand the detrimental effects of climate change on land-based food procurement, but also to understand the complex socio-cultural, economic and environmental challenges related to food security. This study utilizes Indigenous Methodologies to guide all aspects of the research. Evidence was collected using semi-structured interviews with Elders, land-users, and knowledgeable community members. The benefits and difficulties of engaging in land-based and alternative food procurement were key topics explored. Strategies to manage food insecurity, to promote local food procurement and to create a clear picture of community perspectives in addressing constraints to adaptation, were also considered. The results inform policies that reflect the needs of local residents, address the distinct socio-cultural and economic barriers to procure local food and support overall community resilience and adaptive capacities to environmental changes. Food security Climate change Indigenous Rural communities Sub-arctic